Effect of Hot Water Extracts of White Button Mushrooms on Human Aortic Endothelial Cells (HAEC) Exposed to Hyperglycemia (P06-085-19). (13th June 2019) - Martin, Keith
Abstract: Objectives: In the present study, we investigated the effects of WBM on aortic endothelium alone or in a hyperglycemic environment with or without insulin. Methods: Sterile (0.22 um filtered) hot water extracts of WBM (Agaricus bisporus) were added to endothelial basal medium (5% v/v) alone or containing glucose (final concentration 600 mg/dl; 33.3 mM) and/or insulin (100 nM) for 24 hours. Results: We show that WBM increased reactive oxygen species (ROS) levels by 2.5-fold (p < 0.05) compared to control cultures using the DCFH-DA assay, which was further increased 18% with insulin inclusion, but decreased by ∼20% in the presence of glucose with or without insulin. WBM also increased nitric oxide (NO) levels by 4-fold (p < 0.05) compared to control cultures, which was further increased by 3.5-fold in the presence of glucose (p < 0.05) suggesting possible potentiation. We noted no differences in NO production, compared to control cultures, with inclusion of insulin with or without glucose. Viability determined by MTT reduction, was not different between any of the groups. Conclusions: The results suggest that water-soluble components of WBM may modulate ROS and NO production in a hyperglycemic microenvironment and potentially improve endothelial function, in part, via the potential vasorelaxation properties of NO. Funding Sources: Internal Seed Grant, School of Health Studies, University of Memphis, Memphis, TN 38, 152.